A national survey of burnout amongst Canadian Royal College of Physicians and Surgeons of Canada emergency medicine residents - Liu, Robin; Van Aarsen, Kristine; Sedran, Rob; Lim, Rodrick (Canadian Medical Education Journal, 2020)
Background: In recent years, there has been growing interest in the field of physician wellness and burnout. The prevalence of burnout is non-uniform between medical specialties and is most prevalent amongst emergency medicine physicians. Importantly, burnout can be observed amongst individuals early in their medical careers, including medical students and residents. Despite ample studies in other populations, there is no national perspective of burnout amongst Canadian Royal College of Physicians and Surgeons of Canada (RCPSC)Emergency Medicine (EM) residents. Methods: Our study surveyed Canadian residents undergoing EM training though the RCPSC via local program directors using an anonymous electronic form. Basic demographic characteristics and residents’ contemplation of suicide were surveyed. The Maslach Burnout Inventory – Human Services Survey (MBI-HSS) for medical personnel was used to assess burnout on three dimensions (emotional exhaustion, depersonalization and personal accomplishment). Results: A total of 65 valid responses were collected from eight of 14 eligible institutions (response rate = 30%). Respondents are primarily male (58%) and in their postgraduate year (PGY) 1-3 (71%). Overall, 62% of residents met the threshold for burnout according to a widely cited definition of burnout using the MBI-HSS. Additionally, 14% contemplated suicide during their training. There was no statistical significance in burnout rates between male and female responders or between residents in different stages of training. Conclusion: Our results suggest significant burnout amongst Canadian EM residents. These results point to an important opportunity to better support EM residents during their training to improve wellness and reduce burnout.